Poverty measurement revisited from a multidimensional perspective among Universiti Sains Malaysia's B40 poor students - Parthiban S. Gopal (Penerbit Universiti Kebangsaan Malaysia, 2018)
Poverty has been dominantly an economic concept and dealt with income or expenditure in Malaysia. In many parts of the world, widespread support surface for the application of a multidimensional approach to poverty. Yet, in practice the vast majority of empirical work on poverty uses a unidimensional yardstick to judge a person’s well-being, usually expenditure or income per capita. While economic well-being, capability, political, and civic/cultural inclusion are integral parts of a multidimensional concept of poverty, a proper operationalization as well as comprehensive conceptualization of poverty based on multidimensional perspective is still lacking in Malaysia. With the introduction of the Multidimensional Poverty Index (MPI) this paper aims at bridging the gap between development and national policy from a multidimensional perspective. As a review paper, this study intends develop a coherent framework for measuring multidimensional poverty index in a smaller scale among the poor B40 Universiti Sains Malaysia (USM) students. Hence, by understanding the root causes of poverty as well as applying into an academic environment, the study will be able to bridge the gap between student’s academic performance with their quality of life from three major components; education, health and standard of living. The methodology of this paper is based solely on document research of secondary data. The findings of this study are envisaged to ascertain to what extent multidimensional poverty index is valid vis-a-vis the unidimensional measurement approach in the near future for a bigger scale research, both in the state of Penang and other states in Malaysia.